Análise espacial da favorabilidade de ocorrência de cisticercose bovina no Estado do Espírito Santo - Avelar, Barbara Rauta de (2013)
The bovine cysticercosis is a zoonotic parasitic disease with economic importance, caused by the larval stage of Taenia saginata,Cysticercus bovis. The objective of this work was to criate a risk map of the bovine cysticercosis occurrence in the Espírito Santo State . Through a literature review raised the following variables as important for the occurrence of there is parasitosis: sanitary sewage inappropriate (SSI), cattle population by municipality (CPM), use and occupation of the ground (UOG) and flood risk (FR). The database was criate using the data provided by IBGE for SSI and CPM. The data mapping was carried out in the program ArcGIS/ArcInfo 10.1., in which a mathematical model was develop involving the selected variables resulting map risk for the occurrence of bovine cysticercosis in the state. The map showed that the state of Espírito Santo predominate areas medium risk for the occurrence of the parasite, while areas of high and very high risk does not reach 12% of the study area and are mainly located in the northern region in the state. The use of GIS helped in the elucidation of the sites risk of bovine cysticercosis in the Espírito Santo State, and with it, more severe measures of control and prevention of bovine cysticercosis should be directed in the countries of the State with areas of high and very high risk